Disasters of Peace: An Exchange - PULP FICTIONS No.1 - Karin van Marle (Pretoria University Law Press (PULP), 2005)
Disasters of Peace: An Exchange - PULP FICTIONS No.1 Edited by Christof Heyns and Karin van Marle 2005 ISSN: 1992-5174 Pages: 33 Print version: Available Electronic version: Free PDF available